Postpartum nurses' perceptions of barriers to screening for intimate partner violence: a cross-sectional survey - Guillery Margaret E; Benzies Karen M; Mannion Cynthia; Evans Sheila (BMC, 2012)
Abstract Background Intimate partner violence (IPV) is a human rights violation that is pervasive worldwide, and is particularly critical for women during the reproductive period. IPV includes physical, sexual and emotional abuse. Nurses on in-patient postpartum units are well-positioned to screen women for IPV, yet low screening rates suggest that barriers to screening exist. The purpose of this study was to (a) identify the frequency of screening for IPV, (b) the most important barriers to screening, (c) the relationship between the barriers to screening and the frequency of screening for types of abuse, and (d) to identify other factors that contribute to the frequency of screening for IPV. Methods In 2008, we conducted a cross-sectional survey of 96 nurses from postpartum inpatient units in three Canadian urban hospitals. The survey included the Barriers to Abuse Assessment Tool (BAAT), adapted for postpartum nurses (PPN). Ordinary least squares (OLS) regression models were used to predict barriers to screening for each type of IPV. Results The frequency of screening varied by the type of abuse with highest screening rates found for physical and emotional abuse. According to the BAAT-PPN, lack of knowledge was the most important barrier to screening. The BAAT-PPN total score was negatively correlated with screening for physical, sexual, and emotional abuse. Using OLS regression models and after controlling for demographic characteristics, the BAAT-PPN explained 14%, 12%, and 11% of the variance in screening for physical, sexual and emotional abuse, respectively. Fluency in the language of the patient was negatively correlated with screening for each type of abuse. When added as Step 3 to OLS regression models, language fluency was associated with an additional decrease in the likelihood of screening for physical (beta coefficient = -.38, P < .001), sexual (beta coefficient = -.24, P = .05), and emotional abuse (beta coefficient = -.48, P < .001) and increased the variance explained by the model to 25%, 17%, and 31%, respectively. Conclusions Our findings support an inverse relationship between rates of screening for IPV and nurses' perceptions of barriers. Barriers to screening for IPV, particularly related to knowledge and language fluency, need to be addressed to increase rates of screening on postpartum units.